Our Experience of Managing Central Airway Tumors: Anesthesia Perspectives - Thushara Madathil; Devika Poduval; Tony Jose; Nagarjuna Panidapu; Don Jose; Tinku Joseph; Praveen Kumar Neema (Annals of Cardiac Anaesthesia)
Adult patients with central airway tumors commonly present with dyspnea on exertion. These patients may remain asymptomatic until more than half of the airway diameter is obliterated. Anesthesia for debulking a central airway tumor is challenging. Anesthetic management should include a strategy for oxygenation and ventilation, a plan for the same if tumor bleeding aggravates airway obstruction and a plan to deal with acute emergencies like pneumothorax and cardiac arrest. Patients with airway tumors occupying < 50% airway diameter and comfortable during routine activities can be managed using relaxant anesthesia and rigid bronchoscopy for debulking. Airway tumors with >75% airway lumen compromise are the sickest and may present in respiratory failure. We found that in these patients, maintaining spontaneous ventilation, avoidance of general anesthesia, and muscle relaxation are the keys to management. General anesthesia and muscle relaxants decreases / abolishes negative intrapleural pressure, which may result in dynamic hyperinflation and pneumothorax in presence of airway obstruction. In this subset, we routinely use i-gel (sizes 4 and 5) as an airway conduit for debulking. We prefer i-gel® (Intersurgical Ltd, UK) over rigid bronchoscopy as it requires less sedation. To allow this, it is prudent to ensure excellent airway anesthesia prior to i-gel placement using airway blocks, topical anesthetics, and titrated doses of sedation. We manage 20–30 cases of central airway tumors for debulking or stenting every year and share our experience of managing four cases depicting a spectrum of airway and review the literature on anesthetic management of central airway tumors.